Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.

[tex]\frac{1}{\sqrt{3}-1 } +\frac{1}{\sqrt{3}+1 }

Sagot :

[ 1 / √3 - 1 ] + [ 1 / √3 + 1 ] =

[ ( √3 + 1 / √3 + 1 )( 1 / √3 - 1 ) ] +

[ ( 3 - 1 / 3 - 1 )( 1 / √3 + 1 ) ] =

[ √3 + 1 / ( √3 + 1 )( √3 - 1 ) ] +

[ √3 - 1 / ( √3 + 1 )( √3 - 1 ) ] =

√3 + 1 + √3 - 1 / ( √3 + 1 )( √3 - 1 ) =

2√3 / ( √3 )^2 - ( 1 )^2 =

2√3 / 3 - 1 =

2√3 / 2 =

2 × √3 / 2 × 1 =

√3